“Return to the Lord” (Hos 14:3): Repentance as the Essence of the Relationship Between God and Man - Pikor, Wojciech (Collectanea Theologica, 2021)
The article focuses on the theme of return/conversion in the Book of Hosea. The issue is presented from the perspective of the two parties of the covenant: God and Israel. At the starting point lies Israel’s refusal to return to God, and Yahweh’s threatening, punitive retribution to his people. The ending focuses on the conversion of the people to Yahweh, a development possible only owing to God’s preceding forgiveness, expressed by his turn to his people. These four different dynamics of return are reconstructed on the basis of the twenty-two instances of the verb šûb in the Book of Hosea.